Model pemberdayaan kelompok wanita tani (KWT) melalui modal sosial untuk menjaga kohesivitas kelompok: Indonesia - Rili Windiasih; Adhi Iman Sulaiman; Krismiwati Muatip; Lilik Kartika Sari; Rachmi Al Nido (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
This research aims to analyze elements of social capital to maintain groups cohesiveness and designing an empowerment model for Women Farmer Groups (KWT). The research method used is explanatory sequential mixed methods design, a two-stage research process, quantitative descriptive analysis and qualitative analysis. Data collection used census techniques for 30 informants, namely all members of KWT Karya Tani , Katel Klawu Hamlet, Pengalusan Village, Mrebet District, Purbalingga Regency and conducted in-depth interviews with 7 key informants and the KWT chairman and management through Focus Group Discussion (FGD).  The research results show that the elements of social capital consisting of strong networks; trust; compliance with norms; cooperation and social awareness for group members as well as involvement in group activities. are in the high category. The empowerment strategy at KWT Karya Tani to maintain cohesiveness is by integrating closed social capital and open social capital that accommodates the complex, heterogeneous social dynamics of society within the ties of social entities attached to KWT Karya Tani. The majority of KWT Karya Tani members are devout Christians and are bound by the religious norms and community organizations. Each member of KWT Karya Tani is a member of the Jamaat Women's Group as well as the wife of a member of the Karya Tani farmer group. This uniqueness presents empirical findings in the study of the empowerment model that will be implemented at KWT Karya Tani, namely a collaborative all aspect of empowerment model through a holistic, community-based approach.